Keterlibatan Anak dalam Game Simulasi Perang: Tantangan Bahasa dan Komunikasi - Anjarwati, Fitri; Farid, Mujahidin; Adam Zulkepli, Ahmad; Ali, Sakina (EduStream: Jurnal Pendidikan Dasar, 2024)
In an increasingly advanced digital era, online games, particularly war simulation games, have become a popular form of entertainment among children. While these games offer enjoyment and social engagement, negative consequences need to be addressed, particularly regarding language use and aggressive behavior. This study aims to explore the impact of children's involvement in war simulation games on their language development and social interactions. A literature review encompassing previous studies found that exposure to coarse language in games can contribute to the normalization of aggressive behavior and the use of inappropriate language in daily life. Furthermore, the importance of parental and educator roles in guiding children to understand communication boundaries is emphasized. Recommendations for introducing educational games that stimulate creativity and language skills, such as Minecraft and LEGO, are also presented as positive alternatives. Thus, this study concludes that the appropriate selection of games and support from parents can help mitigate negative impacts and support children's overall social and emotional development.